Tradisi, Adat dan Kebudayaan di Desa Talawi Hilie, Kota Sawahlunto, Sumatera Barat - Lisa Putriani; Muhammad Zico; Farhan Ramadhan; Nurul Hikmah; Zulaikha, Zulaikha; Khoirunnisa Heristin (CV. ITTC INDONESIA, 2025)
This community service project was conducted in Talawi Hilie Village, Sawahlunto City, West Sumatra, focusing on the preservation and revitalization of local traditions and cultural heritage. Using ethnographic observation and interviews, the team identified three main cultural components: the Islamic jurisprudence (fiqh) study sessions, the traditional Randai Alang Babega performance, and the historical site of Syekh Tompuo Sakati’s tomb. The fiqh sessions held at Surau Gadang serve as a platform for strengthening religious knowledge and values. The Randai performance functions as both a cultural art and a medium for character education. Additionally, the tomb of Syekh Tompuo is regarded as a valuable religious and historical site by the local community. Through this program, the community was encouraged to preserve and promote these cultural elements as part of their identity and heritage. The results showed a positive response from the locals, increased awareness, and stronger intergenerational cultural transmission.